Novel Approach for Pain Control in Patients Undergoing Prostate Biopsy: Iliohypogastric Nerve Block with or without Topical Application of Prilocaine-Lidocaine: A Randomized Controlled Trial - Hizli, Fatih; Argun, Guldeniz; Ozkul, Fatih; Guven, Oguz; Arik, Ali Ihsan; Basay, Sinan; Kosus, Aydin; Gunaydin, Halil; Basar, Halil (Urology Journal, 2015)
Abstract Purpose: To investigate the efficacy of a novel anesthetic technique called iliohypogastric nerve block (INB) for pain control in patients undergoing prostate biopsy. Materials and Methods: A total of 59 consecutive patients who underwent transrectal ultrasound guided prostates biopsies were included in the study. Patients were randomized into four groups: (1) control, no method of anesthesia was administered, (2) intrarectal prilocaine-lidocaine cream application, (3) INB and (4) INB + intrarectal prilocaine-lidocaine cream application (combined group). Patients were asked to use a scale of 0-10 in a Visual Analogue Scale (VAS) questionnaire about pain during probe insertion (VAS 1) and prostate biopsy (VAS 2). Results: The mean VAS 1 and VAS 2 scores were 0.7 and 4.9 for controls, 0.5 and 1.8 for INB, 0.5 and 2.6 for the intrarectal cream group, and 0.4 and 1.8 for the combined group. The mean VAS 1 scores were not different between groups. However, the mean VAS 2 scores were significantly lower in INB, prilocaine-lidocaine cream and combined groups compared to the control group (P < .001). In addition, the INB group had significantly lower VAS 2 scores compared to the cream application group (P = .03). On the other hand, there was no difference between the INB and combined groups (P = .8). Conclusion: Any form of anesthesia was superior to none. However, INB alone seemed to be superior to prilocaine-lidocaine cream application in patients undergoing prostate biopsy. Addition of prilocaine-lidocaine cream application to INB may not provide better analgesia.